Presence of tannins in sorghum grains is conditioned by different natural alleles of Tannin1 - Wu, Yuye; Li, Xianran; Xiang, Wenwen; Zhu, Chengsong; Lin, Zhongwei; Wu, Yun; Li, Jiarui; Pandravada, Satchidanand; Ridder, Dustan D; Bai, Guihua; Wang, Ming L; Trick, Harold N; et al. (Proceedings of the National Academy of Sciences - PNAS, 2012)
Sorghum, an ancient old-world cereal grass, is the dietary staple of over 500 million people in more than 30 countries in the tropics and semitropics. Its C4 photosynthesis, drought resistance, wide adaptation, and high nutritional value hold the promise to alleviate hunger in Africa. Not present in other major cereals, such as rice, wheat, and maize, condensed tannins (proanthocyanidins) in the pigmented testa of some sorghum cultivars have been implicated in reducing protein digestibility but recently have been shown to promote human health because of their high antioxidant capacity and ability to fight obesity through reduced digestion. Combining quantitative trait locus mapping, meta-quantitative trait locus fine-mapping, and association mapping, we showed that the nucleotide polymorphisms in the Tan1 gene, coding a WD40 protein, control the tannin biosynthesis in sorghum. A 1-bp G deletion in the coding region, causing a frame shift and a premature stop codon, led to a nonfunctional allele, tan1-a . Likewise, a different 10-bp insertion resulted in a second nonfunctional allele, tan1-b . Transforming the sorghum Tan1 ORF into a nontannin Arabidopsis mutant restored the tannin phenotype. In addition, reduction in nucleotide diversity from wild sorghum accessions to landraces and cultivars was found at the region that codes the highly conserved WD40 repeat domains and the C-terminal region of the protein. Genetic research in crops, coupled with nutritional and medical research, could open the possibility of producing different levels and combinations of phenolic compounds to promote human health.